PHYSIOLOGY OF LOCAL BLOOD GOATS - А. У. Торешова; И. Ш. Турсинбаева (Galaxy International Interdisciplinary Research Journal, 2023)
One of the most important components of the internal environment of the animal body is blood, through which all its organs and tissues are combined into a single whole. Indicators of blood, as one of the physiological systems, are an integral indicator of the functioning of the whole organism.